Fabrication of BaTiO3@FeO core-shell nanoceramics for dielectric capacitor applications. (15th April 2021) - Wang, Hongye; Cao, Minghe; Mao, Tenglong; Fu, Jiqing; Pan, Wengao; Hao, Hua; Yao, Zhonghua; Liu, Hanxing
Abstract: Nanoceramics have a wide application in dielectric field due to their excellent dielectric properties.However, it is extremely difficult to fabricate densified BaTiO3 with nanometer scale crystalline. In this study, nanoscaleBaTiO3 ceramics are successfully fabricated by deposition of a FeO layer onto BaTiO3 nanoparticle, and the structure and dielectric behavior of the BaTiO3 @FeO nanoceramics are systematically investigated. The multilayer structure including 1) an inner tetragonal core, 2) a gradient lattice strain layer and 3) a surface insulating layer makes the dielectric constant peak tend to be rounded and broadened. Consequently, an excellent temperature/frequency stability met the X7R requirements and accompanied by the low dielectric loss are achieved in the BaTiO3 @FeO nanoceramics. Grapical abstract: Image, graphical abstract